ANTIPHOSPHOLIPID SYNDROME AND EARLY REPRODUCTIVE FAILURE - M. I. Krivonos; M. S. Zainulina; S. A. Selkov (IRBIS LLC, 2017)
Antiphospholipid antibodies by disrupting trophoblast invasion and endometrial angiogenesis might contribute to a defective placentation and, in turn, affect the successful beginning of pregnancy. It is well known and proven that these processes begin with the founding of the utero-placental blood flow. Given the ability of aPLs to affect implantation and placentation, authors have recently suggested the possibility that aPLs may be responsible also for recurrent implantation failure, early pregnancy loss and unexplained sterility. Possible pathogenic mechanisms: the ability of aPLs to exert a direct negative effect on uterine endothelium and preimplantation embryos, increased activity of NK-cells, increased prothrombotic mechanisms and disruption of the processes of fibrinolysis and fibrin formation.